An atmosphere-pulse energy-scan path synergistically regulated yttrium oxide tungsten alloy wear-resistant coating electric spark deposition method

CN122959655APending Publication Date: 2026-10-23SHENYANG LIGONG UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202611408449.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-11
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

[0011]本发明旨在提供一种气氛-脉冲能量-扫描路径协同调控的含氧化钇钨合金耐磨涂层电火花沉积方法,以解决采用单一气氛和固定放电参数连续沉积时,界面起始成层、主体层材料转移以及末端表面覆盖难以分别调控的问题

Benefits of technology

[0034]1、本发明将电火花沉积划分为界面预沉积、主体沉积和表面覆盖三个阶段,并使局部气氛和放电能量随阶段同步切换,相比采用单一气氛和固定参数连续沉积,可针对各阶段不同功能分别设置工艺条件,实现界面结合、组织致密与表层减摩的协同优化。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122959655A_ABST
    Figure CN122959655A_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of steel component surface wear-resistant coating preparation and electric spark deposition, in particular to an atmosphere-pulse energy-scan path synergistic regulation and control yttria-containing tungsten alloy wear-resistant coating electric spark deposition method. A W-Ni-Fe-Co first tungsten alloy electrode containing nano yttria and a W-Cu second tungsten alloy electrode are used, and the electric spark deposition process is divided into three stages: the first stage is argon-dominant low-energy interface deposition, the second stage is air-dominant medium-high-energy main body deposition, and the third stage is argon-dominant low-energy surface covering. The atmosphere conversion and intermittent cooling are realized by setting stop discharge argon blowing between stages; the three stages adopt 0°, 90°, 45° / 135° cross scanning and increasing track lap rate to improve the uniformity of the coating. The present application forms a yttria-containing tungsten alloy wear-resistant coating metallurgically combined with the substrate on the surface of the steel substrate through the synergistic regulation and control of the stage of atmosphere state, discharge energy, electrode switching and scanning path.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of wear-resistant coating preparation and electro-spark deposition technology for steel component surfaces, specifically a method for electro-spark deposition of wear-resistant coatings on yttrium oxide-containing tungsten alloys with atmosphere-pulse energy-scanning path synergistic control. Background Technology

[0002] Surface wear is one of the common failure modes of steel mechanical components during service. Long-term friction and wear can easily lead to material loss on the surface of components, a decrease in dimensional accuracy, and a shortened service life. Therefore, improving the hardness and wear resistance of steel components through surface strengthening technology is of great significance for extending the service life of parts and reducing maintenance and replacement costs.

[0003] Tungsten and tungsten alloys possess high hardness, melting point, and wear resistance. Depositing them as surface strengthening materials on steel substrates can improve the surface resistance of steel components to plastic deformation and wear. Electrospark deposition technology utilizes instantaneous pulsed discharge between the electrode and the substrate to locally melt the electrode material and transfer it to the substrate surface. This allows for the formation of a reinforced layer bonded to the substrate with minimal thermal impact, making it suitable for localized strengthening and wear-resistant repair of steel component surfaces. However, high-hardness tungsten alloy coatings may still exhibit issues such as microstructure coarsening, localized inhomogeneity, and brittleness during rapid melting and solidification. Under cyclic friction loads, they are prone to localized plastic deformation, microcrack initiation, or abrasive grain detachment, thus limiting further improvements in wear resistance.

[0004] Currently, the preparation of tungsten alloy coatings by electrical discharge deposition (EDD) often employs a single electrode, a single atmosphere, and fixed discharge parameters for continuous deposition. This makes it difficult to simultaneously achieve optimal interfacial bonding quality, substrate density, and surface tribological properties. Excessive energy during the interfacial deposition stage can cause thermal damage to the substrate, while insufficient energy results in inadequate adhesion. In the substrate deposition stage, overly strong atmosphere protection leads to low material transfer efficiency, while insufficient protection easily causes oxidation defects. Furthermore, if only a high-hardness tungsten phase is used for the surface layer, the coefficient of friction is high, resulting in severe wear. Therefore, the key challenge for tungsten alloy wear-resistant coatings is how to maintain the high hardness of the tungsten alloy coating while refining the deposition structure, improving its uniformity and wear resistance through process control, and optimizing the surface tribological interface.

[0005] Yttrium oxide possesses a high melting point and good thermal and chemical stability. Introducing nano-sized yttrium oxide into tungsten alloy systems, during the rapid heating and solidification process of electrospark deposition, allows yttrium oxide particles to increase heterogeneous nucleation sites and inhibit coarsening of the deposited microstructure. Simultaneously, the dispersed distribution of yttrium oxide particles helps restrict dislocation movement and localized plastic deformation, thus potentially improving the microstructure and wear resistance of tungsten alloy coatings. Therefore, introducing an appropriate amount of nano-yttrium oxide into a W-Ni-Fe-Co tungsten alloy sintering electrode and using this electrode for electrospark deposition is a feasible technical approach to improve the overall wear resistance of tungsten alloy coatings. In tungsten-copper alloys, the tungsten component provides wear-resistant support, while the copper component has good plasticity and thermal conductivity. Selectively using it in the low-energy surface coating stage is beneficial for regulating the surface plasticity and friction interface state, allowing for a division of labor between the load-bearing function of the main wear-resistant layer and the surface friction interface regulation function.

[0006] The patent with publication number CN1711366A proposes an electrode material for electrical discharge machining and its manufacturing method. The electrode is used to perform engraving and cutting on the workpiece. The purpose is to reduce the wear of the electrode itself and increase the etching rate. It only improves the material composition of W-Cu electrode and does not involve the coating deposition process at all. It cannot solve the technical problem of preparing wear-resistant coatings on steel surfaces.

[0007] The patent with publication number CN103173641A proposes a method for preparing nano-yttrium oxide dispersion-strengthened tungsten alloy. The method obtains a dense tungsten alloy billet through powder metallurgy sintering. The process is a powder metallurgy route of wet mixing-calcination-reduction-sintering, which does not have surface engineering problems such as interface bonding and surface friction control.

[0008] The patent with publication number CN113106279A proposes a multi-doped oxide dispersion-strengthened tungsten-based alloy and its preparation method and application. Targeting the high-temperature irradiation scenario of fusion reactors, it solves the problem of low-temperature brittleness of bulk materials by using high-energy ball milling and spark plasma sintering processes to generate complex oxide dispersion phases to improve bulk toughness. It does not involve the staged process design of the electrospark deposition coating.

[0009] The patent with publication number CN102190911A proposes a tungsten carbide cobalt-copper-fluoride self-lubricating wear-resistant coating and its preparation method. The coating is a WC-Co ceramic matrix and a fluoride self-lubricating system, and is prepared by atmospheric plasma spraying. However, this is a single-step spraying process, which cannot solve the problem of the difficulty in simultaneously achieving the performance of the interface, the substrate, and the surface layer in electrical spark deposition.

[0010] Therefore, it is necessary to develop a programmed electrospark deposition method suitable for the use of a W-Ni-Fe-Co first tungsten alloy electrode containing nano-yttrium oxide and a W-Cu second tungsten alloy electrode. While maintaining the overall deposition parameter window, the method should coordinately control the local atmosphere, deposition voltage, deposition capacitance, inter-stage pauses, and scanning path in stages to meet different requirements for interface formation, host material transfer, and surface coverage. This will form a wear-resistant yttrium oxide tungsten alloy coating that is metallurgically bonded to the steel substrate and has good wear resistance. Summary of the Invention

[0011] This invention aims to provide an electro-spark deposition method for yttrium oxide-containing tungsten alloy wear-resistant coatings with coordinated control of atmosphere, pulse energy, and scanning path. This addresses the difficulty in separately controlling interface initiation, bulk material transfer, and end-surface coverage during continuous deposition using a single atmosphere and fixed discharge parameters. The invention employs a W-Ni-Fe-Co electrode containing nano-yttrium oxide as the first sintered tungsten alloy electrode and a W-Cu electrode as the second tungsten alloy electrode, wherein the mass fraction of tungsten is 80% and the mass fraction of copper is 20%. The electro-spark deposition is divided into three stages: argon-dominated low-energy interface deposition, air-dominated medium-to-high-energy bulk deposition, and argon-dominated low-energy surface coverage using the second tungsten alloy electrode. Argon purging without discharge is implemented between adjacent stages, and the scanning direction and trajectory overlap rate are varied in each stage, allowing the atmosphere state, discharge heat input, and scanning path to change synergistically with the deposition stage.

[0012] The technical solution of this invention is:

[0013] An electrospark deposition method for wear-resistant coatings on yttrium oxide-containing tungsten alloys with atmosphere-pulse energy-scanning path coordinated control includes the following steps:

[0014] (1) Two tungsten alloy electrodes were prepared: the first tungsten alloy electrode was prepared by pressing and sintering tungsten powder, nickel powder, iron powder, cobalt powder and yttrium oxide powder, wherein the mass fraction of yttrium oxide was 0.5~0.7%, the mass fraction of nickel was 5.25%, the mass fraction of iron was 1.75%, the mass fraction of cobalt was 0.3%, and the balance was tungsten; the second tungsten alloy electrode was a tungsten-copper alloy electrode, wherein the mass fraction of tungsten was 80% and the mass fraction of copper was 20%.

[0015] (2) The steel substrate and the first tungsten alloy electrode and the second tungsten alloy electrode are subjected to surface pretreatment. Before formal deposition, the first tungsten alloy electrode and the second tungsten alloy electrode are pre-discharge activated respectively.

[0016] (3) The steel substrate surface is subjected to first stage, second stage and third stage of electric spark deposition in sequence, wherein: the first stage and second stage use the first tungsten alloy electrode, and the third stage uses the second tungsten alloy electrode;

[0017] The first stage was carried out under an argon-dominant atmosphere, with a deposition voltage of 30–40 V, a deposition capacitance of 60–80 μF, and an effective deposition time of 0.2–0.6 min / cm² per unit area. 2 After the first stage is completed, stop the discharge and perform argon purging for 5-30 seconds.

[0018] The second stage was carried out in an air-dominant atmosphere, with a deposition voltage of 50–70 V, a deposition capacitance of 100–140 μF, and an effective deposition time of 0.6–3.8 min / cm² per unit area. 2 After the second stage is completed, stop the discharge and perform argon purging for 5-30 seconds.

[0019] The third stage was carried out under an argon-dominant atmosphere, with a deposition voltage of 30–45 V, a deposition capacitance of 60–90 μF, and an effective deposition time of 0.2–0.6 min / cm². 2 ;

[0020] The sum of the effective deposition time per unit area for the three depositional stages is 1–5 min / cm. 2 The three deposition stages employ different scanning directions and set trajectory overlap rates to form cross-scanning paths, thereby forming a wear-resistant coating containing yttrium oxide tungsten alloy on the surface of the steel substrate.

[0021] The described electro-spark deposition method for yttrium oxide tungsten alloy wear-resistant coatings, which is synergistically controlled by atmosphere, pulse energy, and scanning path, involves pre-purging the deposition area with argon gas at a flow rate of 5-20 L / min for 30-120 s before formal deposition; the argon gas flow rate during the first and third deposition stages is 5-15 L / min; and the argon gas flow rate during the period between the two stages when discharge is stopped is 5-20 L / min.

[0022] The described atmosphere-pulse energy-scanning path coordinated control method for the electro-spark deposition of yttrium oxide-containing tungsten alloy wear-resistant coatings, when using a capacitor energy storage type electro-spark deposition equipment, uses E=1 / 2CU. 2 The single theoretical energy storage is characterized by C being the deposition capacitance and U being the deposition voltage. The single theoretical energy storage of the second stage is higher than that of the first and third stages, thus forming a low-high-low discharge energy program.

[0023] The described electro-spark deposition method for yttrium oxide-containing tungsten alloy wear-resistant coatings, which is coordinated and controlled by atmosphere, pulse energy, and scanning path, involves three deposition stages with cross-scanning and increasing trajectory overlap rates: the first stage involves parallel scanning along a set 0° direction, with an adjacent trajectory overlap rate of 30-50%; the second stage involves cross-scanning with a 90° rotation relative to the first stage, with an adjacent trajectory overlap rate of 40-70%; and the third stage involves cross-covering scanning with a 45° or 135° direction relative to the first stage, with an adjacent trajectory overlap rate of 50-80%.

[0024] The electro-spark deposition method for wear-resistant coatings of yttrium oxide tungsten alloys with coordinated atmosphere-pulse energy-scanning path control has a trajectory overlap rate η determined by η=(bs) / b×100%, where b is the average width of a single deposition trajectory and s is the distance between the center lines of adjacent deposition trajectories.

[0025] In the electrospark deposition method for wear-resistant coatings of yttrium oxide tungsten alloy with atmosphere-pulse energy-scanning path coordinated control, step (2) involves pre-discharge activation by pre-discharging the first tungsten alloy electrode and the second tungsten alloy electrode on a sacrificial steel sample, respectively. The pre-discharge voltage is 30~40 V, the pre-discharge capacitance is 60~80 μF, and the pre-discharge time is 5~30 s, so that the working ends of the first tungsten alloy electrode and the second tungsten alloy electrode enter a stable discharge state.

[0026] The described electrospark deposition method for a wear-resistant coating of yttrium oxide-containing tungsten alloy, with coordinated control of atmosphere, pulse energy, and scanning path, comprises tungsten powder, nickel powder, iron powder, and cobalt powder in the first tungsten alloy electrode, and tungsten powder and copper powder in the second tungsten alloy electrode, all having a particle size of 40-60 μm. The mixed powder of the two electrodes is pressed at a pressure of 45-55 MPa, and the sintering temperature after pressing is 1500-1600 ℃, with a sintering time of 30-40 min. The yttrium oxide powder has a particle size of 50-100 nm.

[0027] The described electro-spark deposition method for yttrium oxide tungsten alloy wear-resistant coatings, which is synergistically controlled by atmosphere, pulse energy, and scanning path, produces wear-resistant coatings in which Cu can be detected by EDS analysis, and the mass content of Fe is higher than that of W, with an Fe / W mass ratio of 1.01~1.87.

[0028] The described electrospark deposition method for yttrium oxide tungsten alloy wear-resistant coating, which is synergistically controlled by atmosphere, pulse energy, and scanning path, produces a wear-resistant coating containing α-W, α-Fe, γ-Fe(W), and α-Cu phases. The interface between the coating and the steel substrate has a gradient transition zone between W and Fe elements, and the coating thickness is greater than 15 μm.

[0029] The described electro-spark deposition method for yttrium oxide-containing tungsten alloy wear-resistant coatings, with coordinated control of atmosphere, pulse energy, and scanning path, uses CrNi3MoVA steel, No. 45 steel, Q235 steel, 40Cr steel, or H13 steel as the steel substrate. The surface pretreatment of the steel substrate involves sequentially polishing with 240#, 400#, 600#, and 800# sandpaper, polishing with 2.5μm abrasive paste, and ultrasonically cleaning with acetone for 5-15 minutes followed by drying. For the surface pretreatment of the first and second tungsten alloy electrodes, the electrodes are machined into shapes suitable for electro-spark deposition clamping, polished sequentially with 240#, 400#, 600#, and 800# sandpaper, polished with 2.5μm abrasive paste, and then ultrasonically cleaned with acetone for 5-15 minutes followed by drying.

[0030] The design concept of this invention is:

[0031] A first tungsten alloy electrode containing nano-yttrium oxide (YTO) W-Ni-Fe-Co and a second tungsten alloy electrode containing W-Cu were employed. The first electrode, containing YTO, provided a wear-resistant phase, ensuring the hardness and load-bearing capacity of the main coating. The second electrode, W-Cu, was used for surface modification, utilizing the plasticity of copper to optimize the friction interface state and achieve a functional match between the load-bearing capacity of the main body and the friction reduction of the surface. Simultaneously, the electrospark deposition process was divided into three deposition stages with different functions. A YTO-tungsten alloy wear-resistant coating was prepared on the steel substrate surface through localized argon / air staged atmosphere control, staged deposition voltage and capacitance control, inter-stage argon purging, and multi-directional cross-scanning. The first stage, using the first tungsten alloy electrode, was carried out under an argon-dominant atmosphere and low discharge energy, primarily to establish the initial deposition layer and interface transition region. Subsequently, the discharge was stopped and argon purging was performed, allowing the deposition area after the first stage to undergo intermittent cooling without continuous pulsed heat input. The second stage continues to use the first tungsten alloy electrode, switching to an air-dominant atmosphere and increasing the deposition voltage and capacitance as the main deposition stage. This promotes electrode material transfer and the participation of the steel substrate surface material in the transient molten pool mixing, forming the main wear-resistant deposition layer. After the second stage, the discharge is stopped again and argon purging is performed. In the third stage, the second tungsten alloy electrode is used, switching back to an argon-dominant atmosphere and reducing the discharge energy. A high trajectory overlap rate and different scanning directions are used to perform low-energy cross-coverage of the main deposition layer, allowing the W-Cu component to participate in surface regulation and enabling a division of labor between the load-bearing function of the main wear-resistant layer and the friction interface regulation function of the surface coating layer in the third stage. The scanning directions for the three stages are 0°, 90°, and 45° or 135° respectively, so that the subsequent deposition trajectory crosses the area between adjacent deposition trajectories in the previous stage. Through the coordinated regulation of the above atmosphere state, discharge energy, inter-stage thermal history, electrode switching, and scanning path, interface formation, main deposition, and surface coating are completed under the corresponding process conditions.

[0032] The surface and cross-sectional morphology of the coating obtained by the above method show that the deposited layer can continuously cover the steel substrate and form a good bond with the substrate. EDS analysis mainly detected W, Fe, Ni, Cu, Cr, Y, and O elements. Interface line scanning shows that W and Fe elements have a gradient transition in the coating / steel substrate interface region, and Cu element was detected on the coating side. XRD results show that the coating contains α-W, α-Fe, γ-Fe(W), and α-Cu phases. Combined with the hardness and tribological test results, it is shown that the above-mentioned electro-spark deposition method with coordinated control of atmosphere-pulse energy-scanning path can form a wear-resistant yttrium oxide-containing tungsten alloy coating with high hardness, low stable stage friction coefficient, and low wear rate on the surface of the steel substrate.

[0033] The advantages and beneficial effects of this invention are as follows:

[0034] 1. This invention divides electrical discharge deposition into three stages: interface pre-deposition, main body deposition, and surface coating. The local atmosphere and discharge energy are switched synchronously with each stage. Compared with continuous deposition using a single atmosphere and fixed parameters, process conditions can be set separately for different functions of each stage, so as to achieve synergistic optimization of interface bonding, dense structure and surface friction reduction.

[0035] 2. In the first and third stages, the present invention uses argon-dominant atmosphere, and air-dominant atmosphere in the second stage. Argon purging is set between adjacent stages to stop the discharge, so that the atmosphere control can simultaneously perform the functions of deposit environment regulation and inter-stage cooling, without the need to continuously use a closed vacuum environment throughout the entire deposition process.

[0036] 3. This invention employs a low-high-low discharge energy program: the first stage uses 30~40 V and 60~80 μF, the second stage increases to 50~70 V and 100~140 μF, and the third stage decreases to 30~45 V and 60~90 μF, so that interface formation, main material transfer and end coating are at different heat input levels; in the third stage, a second tungsten alloy electrode is replaced, and W-Cu components are introduced for surface coating in a low-energy argon atmosphere, which is beneficial to adjust the state of the friction interface, and the resulting coating exhibits a lower coefficient of friction in the stable stage.

[0037] 4. This invention makes the scanning directions of the three deposition stages intersect each other and sets the trajectory overlap rate for each stage, so that the subsequent deposition trajectory can repeatedly cover the deposition area formed in the previous stage from different directions. This reduces the tendency of directional uneven coverage caused by continuous scanning in a single direction from the process path and improves the overall uniformity of the coating.

[0038] 5. Using the method of the present invention, a W-Ni-Fe-Co nano-yttrium oxide W-Ni-Fe-Co first tungsten alloy sintered electrode and a W-Cu second tungsten alloy electrode can form a deposition layer with a clear W / Fe interface gradient transition on the surface of different steel substrates. EDS detected Cu element, and XRD detected α-W, α-Fe, γ-Fe(W) and α-Cu phases. The hardness of the obtained coating is 10.02~10.48 GPa.

[0039] 6. Under the uniform friction and wear test conditions specified in this invention, the coatings in each embodiment exhibited lower stable-stage friction coefficients and wear rates; for example, the stable-stage friction coefficient of the CrNi3MoVA steel substrate was 0.66, while the stable-stage friction coefficient of its surface coating decreased to 0.27, and the wear rate decreased from 2.8 × 10⁻⁶. -4 mm 3 •N -1 •m -1 Reduced to 3.8×10 -6 mm 3 •N -1 •m -1 This indicates that the above method has a good wear-resistant and friction-reducing effect. Attached Figure Description

[0040] Figure 1 The surface morphology of the wear-resistant coating containing yttrium oxide tungsten alloy deposited by electrical discharge deposition on the surface of CrNi3MoVA steel is shown.

[0041] Figure 2 The figure shows the energy spectrum of region A on the surface of CrNi3MoVA steel with an electrospark-deposited yttrium tungsten oxide alloy wear-resistant coating. In the figure, the horizontal axis represents energy (keV), and the vertical axis represents signal intensity (cps / eV is an abbreviation for counts per second per electron volt).

[0042] Figure 3 The cross-sectional morphology of the wear-resistant coating containing yttrium oxide tungsten alloy deposited by electrical discharge deposition on the surface of CrNi3MoVA steel.

[0043] Figure 4 Line scans show the electrospark deposition of a yttrium tungsten oxide alloy wear-resistant coating on a CrNi3MoVA steel surface. From top to bottom, the curves represent the distribution of Fe, Cu, and W elements. In the figure, the horizontal axis represents the distance (μm) from the substrate to the coating surface, and the vertical axis represents the signal intensity.

[0044] Figure 5 The XRD pattern is shown for the wear-resistant coating containing yttrium tungsten oxide alloy deposited by electrical discharge machining on the surface of CrNi3MoVA steel. In the figure, the horizontal axis represents the diffraction angle (°), and the vertical axis represents the relative intensity (au).

[0045] Figure 6 This figure compares the friction coefficients of a CrNi3MoVA steel substrate and its surface with a yttrium tungsten oxide alloy wear-resistant coating. In the figure, the horizontal axis represents time (min), and the vertical axis represents the friction coefficient.

[0046] Figure 7 This figure compares the wear rates of a CrNi3MoVA steel substrate and its surface yttrium tungsten oxide alloy wear-resistant coating. In the figure, the horizontal axis represents the wear objects: CrNi3MoVA steel and the yttrium tungsten oxide alloy wear-resistant coating, respectively; the vertical axis represents the wear rate (×10). -4 mm 3 •N -1 •m -1 ).

[0047] Figure 8 This is a schematic diagram of the three-stage programmed electrical discharge deposition process of the present invention, wherein the third stage uses a tungsten-copper alloy as the second tungsten alloy electrode.

[0048] Figure 9 This is a schematic diagram illustrating the changes in atmosphere state, discharge energy, and scanning direction with the deposition stage in this invention. Detailed Implementation

[0049] In its specific implementation, this invention employs a W-Ni-Fe-Co sintered first tungsten alloy electrode containing nano-yttrium oxide and a W-Cu second tungsten alloy electrode. A three-stage electro-spark deposition method, synergistically controlled by atmosphere, pulse energy, and scanning path, is used to prepare a wear-resistant coating containing yttrium oxide tungsten alloy on a steel substrate. Before deposition, both electrodes are pre-discharge activated, and the deposition area is pre-purged with argon gas. During deposition, the following steps are performed sequentially: argon-dominated low-energy interface deposition, argon purging between discharge-free stages, air-dominated medium-high energy bulk deposition, argon purging between discharge-free stages, and argon-dominated low-energy surface covering after replacing the second tungsten alloy electrode. The three deposition stages employ scanning directions of 0°, 90°, and 45° or 135° to form a cross-scanning path. The first tungsten alloy electrode is made by pressing and sintering tungsten powder, nickel powder, iron powder, cobalt powder and yttrium oxide powder, wherein the mass fraction of yttrium oxide is 0.5~0.7%, the mass fraction of nickel is 5.25%, the mass fraction of iron is 1.75%, the mass fraction of cobalt is 0.3%, and the remainder is tungsten; the second tungsten alloy electrode is made by pressing and sintering tungsten powder and copper powder, wherein the mass fraction of tungsten is 80% and the mass fraction of copper is 20%.

[0050] like Figure 8As shown, the three-stage programmed electrospark deposition process of this invention is as follows: steel substrate / electrode pretreatment → electrode pre-discharge activation → argon pre-purging → first stage argon low-energy 0° scan → discharge stop + argon purging → second stage high-energy 90° scan in air → discharge stop + argon purging → third stage argon low-energy 45° / 135° scan → obtaining a wear-resistant coating. Specifically, the first stage argon low-energy interface deposition: low energy reduces thermal damage to the substrate, argon protection prevents oxidation, and forms a continuous metallurgical bonding interface; the second stage high-energy bulk deposition in air: increased energy promotes material transfer and molten pool mixing, air environment regulates solidification behavior, forming a dense bulk wear-resistant layer; the third stage argon low-energy surface covering: switching to W-Cu electrodes, achieving surface modification at low energy, and optimizing tribological properties. The inter-stage discharge stop + argon purging simultaneously achieves atmosphere switching and intermittent cooling, suppressing microstructure coarsening; the three-stage cross-scanning and increasing trajectory overlap rate eliminate uneven coverage in unidirectional scanning, improving coating uniformity.

[0051] like Figure 9 As shown, the sequence of changes in atmosphere state, discharge energy, and scanning direction with the deposition stage is as follows: atmosphere state changes from argon → air → argon; discharge energy changes from low → high → low; and scanning direction changes from 0° → 90° → 45° / 135°, corresponding to the synergistic change pattern of the three deposition stages. Two intermittent cooling cycles correspond to the cessation of discharge and argon purging, reflecting the functional correspondence between the low-high-low energy sequence and the interface-substrate-surface layer. After the steel substrate and two types of electrodes undergo surface pretreatment and pre-discharge activation, the deposition area is first pre-purged with argon gas. Then, the following steps are performed sequentially: the first stage of argon-dominated low-energy interface deposition, the first inter-stage argon purging without discharge, the second stage of air-dominated medium-high energy deposition, the second inter-stage argon purging without discharge, and the third stage of argon-dominated low-energy surface coverage using a second tungsten alloy electrode.

[0052] The yttrium oxide-containing tungsten alloy wear-resistant coating of this invention is a metallurgical composite coating formed by the sequential electrospark deposition of a W-Ni-Fe-Co first tungsten alloy sintered electrode and a W-Cu second tungsten alloy electrode, followed by metallurgical mixing in a molten pool. During the third-stage deposition process, local pulse discharge remelts the surface layer of the main coating formed in the first two stages, causing the W and Cu components of the second tungsten copper electrode to fuse with the original coating components. The coating simultaneously contains yttrium oxide, Ni, and Co components from the first tungsten alloy electrode and Cu components from the second tungsten copper electrode, with Cu element distribution throughout the coating thickness direction. The formed wear-resistant coating contains α-W, α-Fe, γ-Fe(W), and α-Cu phases, and the interface between the coating and the steel substrate has a gradient transition zone of W and Fe elements. The coating thickness is greater than 15 μm.

[0053] The "argon-dominated atmosphere" described in this invention refers to the continuous supply of argon gas to the discharge zone under open or locally protected conditions, making the local atmosphere of the discharge zone dominated by argon gas; the "air-dominated atmosphere" refers to stopping the main argon gas supply, allowing the discharge zone to return to ambient air dominance. The effective deposition time per unit area does not include the time for two non-discharge argon gas purging cycles. The trajectory overlap rate η = (bs) / b × 100%, where b is the average width of a single deposition trajectory (mm), and s is the distance between the centerlines of adjacent trajectories (mm). When using a capacitor energy storage device, E = 1 / 2CU can be used. 2 The single-stage theoretical energy storage is characterized, where E is the single-stage theoretical energy storage (J), C is the deposition capacitance (μF), and U is the deposition voltage (V). The theoretical energy storage in the second stage is higher than that in the first and third stages, forming a low-high-low discharge energy program. This invention forms a tungsten alloy wear-resistant coating on the surface of a steel substrate by controlling the local atmosphere, deposition voltage, deposition capacitance, inter-stage argon purging, electrode switching, and scanning path in stages.

[0054] The present invention will now be described in further detail with reference to the accompanying drawings and embodiments:

[0055] Example 1

[0056] The matrix material is CrNi3MoVA steel. The electrodes are made by pressing and sintering a first tungsten alloy electrode with tungsten powder (40-60 μm particle size), nickel powder (40-60 μm particle size), iron powder (40-60 μm particle size), cobalt powder (40-60 μm particle size), and yttrium oxide powder (50-100 nm particle size). The first tungsten alloy electrode contains 0.5% yttrium oxide, 5.25% nickel, 1.75% iron, 0.3% cobalt, and the remainder is tungsten. The second tungsten alloy electrode is made by pressing and sintering a second tungsten alloy electrode with tungsten powder (40-60 μm particle size) and copper powder (40-60 μm particle size). The second tungsten alloy electrode contains 80% tungsten and 20% copper. The pressing pressure for both electrodes is 50 MPa, the sintering temperature after pressing is 1550 ℃, and the sintering time is 30 min.

[0057] In this embodiment, the preparation steps of the yttrium oxide tungsten alloy wear-resistant coating are as follows:

[0058] (1) First, the substrate material is polished step by step with sandpaper of 240#, 400#, 600# and 800# to remove the oxide film on the surface of the substrate. Then, polishing is performed with polishing paste with a particle size of 2.5 μm. Next, ultrasonic cleaning is performed with acetone for 10 min to remove surface oil.

[0059] (2) The first and second tungsten alloy electrodes are both processed into Φ3 mm×20 mm columnar shapes and polished step by step with 240#, 400#, 600# and 800# sandpaper to remove the oxide film on the electrode surface. Then, polishing is performed with polishing paste with a particle size of 2.5 μm. Then, ultrasonic cleaning is performed with acetone for 10 min to remove surface oil.

[0060] (3) Before formal deposition, the first and second tungsten alloy electrodes were pre-discharged at 35 V and 70 μF for 15 s on sacrificial steel specimens, respectively; then the area to be deposited was purged with argon at 10 L / min for 60 s, followed by three-stage electric spark deposition. The first and second stages used the first tungsten alloy electrode, and the third stage used the second tungsten alloy electrode. In the first stage, low-energy interface deposition was carried out in an argon-dominated atmosphere, with a deposition voltage of 35 V, a deposition capacitance of 70 μF, and an effective deposition time per unit area of ​​0.4 min / cm². 2 The system scans along the 0° direction with an overlap rate of 40% between adjacent trajectories. After the first stage, discharge is stopped, and the system is purged for 15 seconds under argon gas at a flow rate of 10 L / min. In the second stage, the main argon gas supply is stopped, and high-energy bulk deposition is performed under an air-dominated atmosphere. The deposition voltage is 50 V, the deposition capacitance is 100 μF, and the effective deposition time per unit area is 2.2 min / cm². 2 The system scans along a 90° direction, with an overlap rate of 55% between adjacent trajectories. After the second stage, discharge is stopped, and the system is purged with argon gas at 10 L / min for 15 s. In the third stage, argon gas is restored at 10 L / min, and low-energy surface coverage is performed under an argon-dominant atmosphere. The deposition voltage is 40 V, the deposition capacitance is 80 μF, and the effective deposition time per unit area is 0.4 min / cm². 2 Scanning along a 45° direction, the overlap rate of adjacent trajectories was 60%. The total effective deposition time per unit area for the three stages was 3 min / cm. 2 .

[0061] The hardness of the yttrium oxide tungsten alloy wear-resistant coating is approximately 10.03 GPa.

[0062] like Figure 1 The image shows the surface morphology of an electrospark-deposited yttrium tungsten oxide alloy wear-resistant coating on a CrNi3MoVA steel surface. (The image is derived from...) Figure 1 It can be seen that the surface of the yttrium oxide tungsten alloy wear-resistant coating has irregular areas formed by the rapid solidification of locally molten material and obvious surface undulations. Area A in the figure is the energy dispersive spectroscopy (EDS) analysis area.

[0063] like Figure 2 As shown, the surface region A of the CrNi3MoVA steel surface is subjected to electrospark deposition of a yttrium tungsten oxide alloy wear-resistant coating. Figure 1 Energy spectrum. Figure 2It can be seen that under the test conditions, EDS mainly detected W, Fe, Ni, Cu, Cr, Y, and O elements, of which: the mass fraction of tungsten was 39.93%, the mass fraction of iron was 40.52%, the mass fraction of nickel was 3.94%, the mass fraction of copper was 14.26%, the mass fraction of chromium was 0.42%, the mass fraction of yttrium was 0.14%, and the mass fraction of oxygen was 0.79%.

[0064] like Figure 3 The cross-sectional morphology of an electrospark-deposited yttrium tungsten oxide alloy wear-resistant coating on the surface of CrNi3MoVA steel is shown. Figure 3 It can be seen that the coating has a dense structure, good adhesion to the substrate, and a thickness greater than 15 μm.

[0065] like Figure 4 The image shows a line scan of the electrospark deposition of a yttrium tungsten oxide alloy wear-resistant coating on the surface of CrNi3MoVA steel. (Source: [Insert image here]) Figure 4 It can be seen that W and Fe elements exhibit a gradient transition at the interface, indicating that the coating and the substrate form a metallurgical bond; at the same time, Cu elements were detected on the coating side.

[0066] like Figure 5 The image shows the XRD pattern of an electrospark-deposited yttrium tungsten oxide alloy wear-resistant coating on a CrNi3MoVA steel surface. (Source: [Insert XRD pattern here]) Figure 5 It can be seen that the coating contains α-W, α-Fe, γ-Fe(W) and α-Cu phases.

[0067] like Figure 6 The figure shows a comparison of the friction coefficients of a CrNi3MoVA steel substrate and its surface yttrium tungsten oxide alloy wear-resistant coating. An HSR-2M tribological testing machine was used, with the following conditions: reciprocating distance 10 mm, reciprocating speed 5 m / min, load 6 N, and friction time 20 min. The workpiece was a Φ6 mm GCr15 steel ball. Figure 6 It can be seen that the friction coefficient of the CrNi3MoVA steel substrate in the stable stage is 0.66, while the friction coefficient of the wear-resistant coating surface containing yttrium oxide tungsten alloy in the stable stage is about 0.27, and the friction coefficient fluctuates little.

[0068] like Figure 7 The figure shows a comparison of the wear rates of the CrNi3MoVA steel substrate and its surface wear-resistant coating containing yttrium tungsten oxide. The wear rate of the CrNi3MoVA steel is 2.8 × 10⁻⁶. -4 mm 3 •N -1 •m -1 The wear rate of the yttrium tungsten oxide alloy wear-resistant coating is only 3.8 × 10⁻⁶. -6 mm 3 •N -1 •m-1 .

[0069] Example 2

[0070] The matrix material is 45# steel. The electrodes are made by pressing and sintering a first tungsten alloy electrode with tungsten powder (40~60 μm particle size), nickel powder (40~60 μm particle size), iron powder (40~60 μm particle size), cobalt powder (40~60 μm particle size), and yttrium oxide powder (50~100 nm particle size). The first tungsten alloy electrode contains 0.5% yttrium oxide, 5.25% nickel, 1.75% iron, 0.3% cobalt, and the remainder is tungsten. The second tungsten alloy electrode is made by pressing and sintering a second tungsten alloy electrode with tungsten powder (40~60 μm particle size) and copper powder (40~60 μm particle size). The second tungsten alloy electrode contains 80% tungsten and 20% copper. The pressing pressure for both electrodes is 50 MPa, the sintering temperature after pressing is 1550 ℃, and the sintering time is 35 min.

[0071] In this embodiment, the preparation steps of the yttrium oxide tungsten alloy wear-resistant coating are as follows:

[0072] (1) First, the substrate material is polished step by step with sandpaper of 240#, 400#, 600# and 800# to remove the oxide film on the surface of the substrate. Then, polishing is performed with polishing paste with a particle size of 2.5 μm. Next, ultrasonic cleaning is performed with acetone for 8 min to remove surface oil.

[0073] (2) The first and second tungsten alloy electrodes are both processed into Φ3 mm×20 mm columnar shapes and polished step by step with 240#, 400#, 600# and 800# sandpaper to remove the oxide film on the electrode surface. Then, polishing is performed with polishing paste with a particle size of 2.5 μm. Finally, ultrasonic cleaning is performed with acetone for 8 min to remove surface oil.

[0074] (3) Before formal deposition, the first and second tungsten alloy electrodes were activated by pre-discharging at 35 V and 70 μF for 15 s on sacrificial steel specimens, respectively; then the area to be deposited was purged with argon at 5 L / min for 30 s, followed by three-stage electric spark deposition. The first tungsten alloy electrode was used in the first and second stages, and the second tungsten alloy electrode was used in the third stage. In the first stage, low-energy interface deposition was carried out in an argon-dominated atmosphere, with a deposition voltage of 30 V, a deposition capacitance of 60 μF, and an effective deposition time per unit area of ​​0.4 min / cm². 2The system scans along the 0° direction with an overlap rate of 30% between adjacent trajectories. After the first stage, discharge is stopped, and the system is purged for 5 seconds under argon gas at a flow rate of 5 L / min. In the second stage, the main argon gas supply is stopped, and medium-to-high energy bulk deposition is performed under an air-dominated atmosphere. The deposition voltage is 50 V, the deposition capacitance is 100 μF, and the effective deposition time per unit area is 2.2 min / cm². 2 The system scans along a 90° direction, with an overlap rate of 40% between adjacent trajectories. After the second stage, discharge is stopped, and the system is purged with argon gas at a rate of 5 L / min for 5 s. In the third stage, argon gas is restored at a rate of 5 L / min, and low-energy surface coverage is performed under an argon-dominant atmosphere. The deposition voltage is 30 V, the deposition capacitance is 60 μF, and the effective deposition time per unit area is 0.4 min / cm². 2 Scanning along a 135° direction, the overlap rate of adjacent trajectories was 50%. The total effective deposition time per unit area for the three stages was 3 min / cm. 2 .

[0075] The hardness of the yttrium oxide-containing tungsten alloy wear-resistant coating is approximately 10.38 GPa. EDS analysis mainly detected W, Ni, Fe, Cu, Co, Y, and O elements, with the following mass fractions: tungsten 32.36%, nickel 2.83%, iron 48.70%, copper 14.26%, cobalt 0.40%, yttrium 0.11%, and oxygen 1.34%.

[0076] The HSR-2M tribological testing machine was used, with the following conditions: reciprocating distance 10 mm, reciprocating speed 5 m / min, load 6 N, and friction time 20 min. The wear parts were Φ6 mm GCr15 steel balls. The coefficient of friction for the 45 steel in the stable stage was 0.68, while the coefficient of friction for the 45 steel with an electrospark deposited yttrium tungsten oxide alloy wear-resistant coating was close to 0.32. The wear rate of the 45 steel was 2.5 × 10⁻⁶. -4 mm 3 •N -1 •m -1 The wear rate of 45 steel with an electrospark-deposited yttrium tungsten oxide alloy wear-resistant coating was only 2.7 × 10⁻⁶. -6 mm 3 •N -1 •m -1 .

[0077] Example 3

[0078] The matrix material is Q235 steel. The electrodes are made by pressing and sintering a first tungsten alloy electrode with tungsten powder (40-60 μm particle size), nickel powder (40-60 μm particle size), iron powder (40-60 μm particle size), cobalt powder (40-60 μm particle size), and yttrium oxide powder (50-100 nm particle size). The first tungsten alloy electrode contains 0.7% yttrium oxide, 5.25% nickel, 1.75% iron, 0.3% cobalt, and the remainder is tungsten. The second tungsten alloy electrode is made by pressing and sintering a second tungsten alloy electrode with tungsten powder (40-60 μm particle size) and copper powder (40-60 μm particle size). The second tungsten alloy electrode contains 80% tungsten and 20% copper. The pressing pressure for both electrodes is 50 MPa, the sintering temperature after pressing is 1500 ℃, and the sintering time is 40 min.

[0079] In this embodiment, the preparation steps of the yttrium oxide tungsten alloy wear-resistant coating are as follows:

[0080] (1) First, the substrate material is polished step by step with sandpaper of 240#, 400#, 600# and 800# to remove the oxide film on the surface of the substrate. Then, polishing is performed with polishing paste with a particle size of 2.5 μm. Then, ultrasonic cleaning is performed with acetone for 9 min to remove surface oil.

[0081] (2) The first and second tungsten alloy electrodes are both processed into Φ3 mm×20 mm columnar shapes and polished step by step with 240#, 400#, 600# and 800# sandpaper to remove the oxide film on the electrode surface. Then, they are polished with polishing paste with a particle size of 2.5 μm and then ultrasonically cleaned with acetone for 9 min to remove surface oil.

[0082] (3) Before formal deposition, the first and second tungsten alloy electrodes were activated by pre-discharging at 35 V and 70 μF for 15 s on a sacrificial steel sample, respectively; then, the area to be deposited was purged with argon at 20 L / min for 120 s, followed by three-stage electric spark deposition. The first tungsten alloy electrode was used in the first and second stages, and the second tungsten alloy electrode was used in the third stage. In the first stage, argon was used to maintain an argon-dominant atmosphere for low-energy interface deposition, with a deposition voltage of 40 V, a deposition capacitance of 80 μF, and an effective deposition time per unit area of ​​0.4 min / cm². 2 The system scans along the 0° direction with a 50% overlap rate between adjacent trajectories. After the first stage, discharge is stopped, and the system is purged for 30 seconds under argon gas at a flow rate of 20 L / min. In the second stage, the main argon gas supply is stopped, and medium-to-high energy bulk deposition is performed under an air-dominated atmosphere. The deposition voltage is 50 V, the deposition capacitance is 140 μF, and the effective deposition time per unit area is 2.2 min / cm². 2The system scans along a 90° direction, with an overlap rate of 70% between adjacent trajectories. After the second stage, discharge is stopped, and the system is purged with argon gas at 20 L / min for 30 s. In the third stage, argon gas is restored at 15 L / min, and low-energy surface coverage is performed under an argon-dominant atmosphere. The deposition voltage is 45 V, the deposition capacitance is 90 μF, and the effective deposition time per unit area is 0.4 min / cm². 2 Scanning along a 45° direction, the overlap rate of adjacent trajectories was 75%. The total effective deposition time per unit area for the three stages was 3 min / cm. 2 .

[0083] The hardness of the yttrium oxide tungsten alloy wear-resistant coating is approximately 10.40 GPa. EDS analysis mainly detected W, Ni, Fe, Cu, Co, Y, and O elements, with the following mass fractions: tungsten 28.84%, nickel 3.67%, iron 51.19%, copper 14.26%, cobalt 0.35%, yttrium 0.09%, and oxygen 1.60%.

[0084] The HSR-2M tribological testing machine was used, with the following tribological conditions: reciprocating distance 10 mm, reciprocating speed 5 m / min, load 6 N, and friction time 20 min. The wear parts were Φ6 mm GCr15 steel balls. The stable stage friction coefficient of Q235 steel was 0.71, while the stable stage friction coefficient of Q235 steel with an electrospark deposited yttrium tungsten oxide alloy wear-resistant coating was close to 0.36. The wear rate of Q235 steel was 2.1 × 10⁻⁶. -4 mm 3 •N -1 •m -1 The wear rate of Q235 steel with an electrically spark-deposited yttrium tungsten oxide alloy wear-resistant coating is only 3.3 × 10⁻⁶. -6 mm 3 •N -1 •m -1 .

[0085] Example 4

[0086] The matrix material is 40Cr steel. The electrodes are made by pressing and sintering a first tungsten alloy electrode with tungsten powder (40-60 μm particle size), nickel powder (40-60 μm particle size), iron powder (40-60 μm particle size), cobalt powder (40-60 μm particle size), and yttrium oxide powder (50-100 nm particle size). The first tungsten alloy electrode contains 0.6% yttrium oxide, 5.25% nickel, 1.75% iron, 0.3% cobalt, and the remainder is tungsten. The second tungsten alloy electrode is made by pressing and sintering a second tungsten alloy electrode with tungsten powder (40-60 μm particle size) and copper powder (40-60 μm particle size). The second tungsten alloy electrode contains 80% tungsten and 20% copper. The pressing pressure for both electrodes is 55 MPa, the sintering temperature after pressing is 1550 ℃, and the sintering time is 30 min.

[0087] In this embodiment, the preparation steps of the yttrium oxide tungsten alloy wear-resistant coating are as follows:

[0088] (1) First, the substrate material is polished step by step with sandpaper of 240#, 400#, 600# and 800# to remove the oxide film on the surface of the substrate. Then, polishing is performed with polishing paste with a particle size of 2.5 μm. Then, ultrasonic cleaning is performed with acetone for 12 min to remove surface oil.

[0089] (2) The first and second tungsten alloy electrodes are both processed into Φ3 mm×20 mm columnar shapes and polished step by step with 240#, 400#, 600# and 800# sandpaper to remove the oxide film on the electrode surface. Then, polishing is performed with polishing paste with a particle size of 2.5 μm. Finally, ultrasonic cleaning is performed with acetone for 12 min to remove surface oil.

[0090] (3) Before formal deposition, the first and second tungsten alloy electrodes were pre-discharged at 35 V and 70 μF for 15 s on sacrificial steel specimens, respectively; then the area to be deposited was purged with argon at 15 L / min for 90 s, followed by three-stage electric spark deposition. The first tungsten alloy electrode was used in the first and second stages, and the second tungsten alloy electrode was used in the third stage. In the first stage, low-energy interface deposition was carried out in an argon-dominated atmosphere, with a deposition voltage of 40 V, a deposition capacitance of 80 μF, and an effective deposition time per unit area of ​​0.6 min / cm. 2 The system scans along the 0° direction with a 50% overlap rate between adjacent trajectories. After the first stage, discharge is stopped, and the system is purged for 20 seconds under argon gas at 15 L / min. In the second stage, the main argon gas supply is stopped, and high-energy bulk deposition is performed under an air-dominated atmosphere. The deposition voltage is 70 V, the deposition capacitance is 100 μF, and the effective deposition time per unit area is 3.8 min / cm². 2The system scans along a 90° direction, with an overlap rate of 60% between adjacent trajectories. After the second stage, discharge is stopped, and the system is purged with argon gas at 15 L / min for 20 s. In the third stage, argon gas is restored at 15 L / min, and low-energy surface coverage is performed under an argon-dominant atmosphere. The deposition voltage is 45 V, the deposition capacitance is 90 μF, and the effective deposition time per unit area is 0.6 min / cm². 2 Scanning along a 135° direction, the overlap rate of adjacent trajectories was 70%. The total effective deposition time per unit area for the three stages was 5 min / cm. 2 .

[0091] The hardness of the yttrium oxide-containing tungsten alloy wear-resistant coating is approximately 10.02 GPa. EDS analysis mainly detected W, Ni, Fe, Cu, Co, Y, and O elements, with the following mass fractions: tungsten 28.11%, nickel 3.31%, iron 52.50%, copper 14.26%, cobalt 0.33%, yttrium 0.15%, and oxygen 1.34%.

[0092] The HSR-2M tribological testing machine was used, with the following conditions: reciprocating distance 10 mm, reciprocating speed 5 m / min, load 6 N, and friction time 20 min. The wear parts were Φ6 mm GCr15 steel balls. The stable stage friction coefficient of 40Cr steel was 0.71, while the stable stage friction coefficient of 40Cr steel with an electrospark deposited yttrium tungsten oxide alloy wear-resistant coating was close to 0.42. The wear rate of 40Cr steel was 2.6 × 10⁻⁶. -4 mm 3 •N -1 •m -1 The wear rate of 40Cr steel with an electrospark-deposited yttrium tungsten oxide alloy wear-resistant coating was only 3.4 × 10⁻⁶. -6 mm 3 •N -1 •m -1 .

[0093] Example 5

[0094] The matrix material is H13 steel. The electrodes are made by pressing and sintering a first tungsten alloy electrode with tungsten powder (40-60 μm particle size), nickel powder (40-60 μm particle size), iron powder (40-60 μm particle size), cobalt powder (40-60 μm particle size), and yttrium oxide powder (50-100 nm particle size). The first tungsten alloy electrode contains 0.7% yttrium oxide, 5.25% nickel, 1.75% iron, 0.3% cobalt, and the remainder is tungsten. The second tungsten alloy electrode is made by pressing and sintering a second tungsten alloy electrode with tungsten powder (40-60 μm particle size) and copper powder (40-60 μm particle size). The second tungsten alloy electrode contains 80% tungsten and 20% copper. The pressing pressure for both electrodes is 45 MPa, the sintering temperature after pressing is 1600 ℃, and the sintering time is 30 min.

[0095] In this embodiment, the preparation steps of the yttrium oxide tungsten alloy wear-resistant coating are as follows:

[0096] (1) First, the substrate material is polished step by step with sandpaper of 240#, 400#, 600# and 800# to remove the oxide film on the surface of the substrate. Then, polishing is performed with polishing paste with a particle size of 2.5 μm. Then, ultrasonic cleaning is performed with acetone for 15 min to remove surface oil.

[0097] (2) The first and second tungsten alloy electrodes are both processed into Φ3 mm×20 mm columnar shapes and polished step by step with 240#, 400#, 600# and 800# sandpaper to remove the oxide film on the electrode surface. Then, polishing is performed with polishing paste with a particle size of 2.5 μm. Then, ultrasonic cleaning is performed with acetone for 15 min to remove surface oil.

[0098] (3) Before formal deposition, the first and second tungsten alloy electrodes were activated by pre-discharging at 35 V and 70 μF for 15 s on sacrificial steel specimens, respectively; then, the area to be deposited was purged with argon at 5 L / min for 30 s, followed by three-stage electrospark deposition. The first and second stages used the first tungsten alloy electrode, and the third stage used the second tungsten alloy electrode. In the first stage, low-energy interface deposition was carried out in an argon-dominated atmosphere, with a deposition voltage of 30 V, a deposition capacitance of 60 μF, and an effective deposition time per unit area of ​​0.2 min / cm². 2 The system scans along the 0° direction with an overlap rate of 30% between adjacent trajectories. After the first stage, discharge is stopped, and the system is purged for 5 seconds under argon gas at a flow rate of 5 L / min. In the second stage, the main argon gas supply is stopped, and high-energy bulk deposition is performed under an air-dominated atmosphere. The deposition voltage is 50 V, the deposition capacitance is 100 μF, and the effective deposition time per unit area is 0.6 min / cm². 2The system scans along a 90° direction, with an overlap rate of 40% between adjacent trajectories. After the second stage, discharge is stopped, and the system is purged with argon gas at a rate of 5 L / min for 5 s. In the third stage, argon gas is restored at a rate of 5 L / min, and low-energy surface coverage is performed under an argon-dominant atmosphere. The deposition voltage is 30 V, the deposition capacitance is 60 μF, and the effective deposition time per unit area is 0.2 min / cm². 2 Scanning along a 45° direction, the overlap rate of adjacent trajectories is 50%. The total effective deposition time per unit area for the three stages is 1 min / cm. 2 .

[0099] The hardness of the yttrium oxide tungsten alloy wear-resistant coating is approximately 10.48 GPa. EDS analysis mainly detected W, Ni, Fe, Cu, Co, Y, and O elements, with the following mass fractions: tungsten 31.45%, nickel 5.02%, iron 46.97%, copper 14.26%, cobalt 0.45%, yttrium 0.13%, and oxygen 1.72%.

[0100] The HSR-2M tribological testing machine was used, with the following conditions: reciprocating distance 10 mm, reciprocating speed 5 m / min, load 6 N, and friction time 20 min. The workpiece was a Φ6 mm GCr15 steel ball. The friction coefficient of H13 steel in the stable stage was 0.69, while the friction coefficient of H13 steel with an electrospark deposited yttrium tungsten oxide alloy wear-resistant coating was close to 0.34 in the stable stage. The wear rate of H13 steel was 4.1 × 10⁻⁶. -4 mm 3 •N -1 •m -1 The wear rate of H13 steel with an electrospark-deposited yttrium tungsten oxide alloy wear-resistant coating was only 5.5 × 10⁻⁶. -6 mm 3 •N -1 •m -1 .

[0101] The results of the examples show that by using a W-Ni-Fe-Co first tungsten alloy sintered electrode containing nano-yttrium oxide and a W-Cu second tungsten alloy electrode, and employing a three-stage atmosphere-pulse energy-scanning path synergistic control of electric spark deposition method—including argon-dominated low-energy interface deposition, argon purging during the no-discharge stage, air-dominated medium-high energy bulk deposition, argon purging during the no-discharge stage, and argon-dominated low-energy surface coverage—a yttrium oxide-containing tungsten alloy wear-resistant coating with obvious interface element transition characteristics can be formed on the surface of different steel substrates. The examples demonstrate that by synergistic control of atmosphere state, discharge energy, electrode switching, and scanning path in stages, a yttrium oxide-containing tungsten alloy wear-resistant coating metallurgically bonded to the substrate is formed on the steel substrate surface. The resulting coating has a hardness of 10.02~10.48 GPa and exhibits a low stable-stage friction coefficient and wear rate under specified friction and wear conditions.

[0102] The above description is merely a specific embodiment of the present invention and should not be construed as limiting the scope of the invention. The yttrium oxide-containing tungsten alloy wear-resistant coating, when applied to the surface of steel components, can significantly improve the wear resistance of the steel components and can be used in fields such as petroleum, military, power, and aerospace. Therefore, various corresponding changes and modifications made based on the technical solution and concept of the present invention still fall within the scope of protection covered by the present invention.

Claims

1. A method for atmosphere-pulse energy-scan path synergistically regulated yttrium-oxide-containing tungsten alloy wear-resistant coating electric spark deposition, characterized in that, Includes the following steps: (1) Two tungsten alloy electrodes were prepared: the first tungsten alloy electrode was prepared by pressing and sintering tungsten powder, nickel powder, iron powder, cobalt powder and yttrium oxide powder, wherein the mass fraction of yttrium oxide was 0.5~0.7%, the mass fraction of nickel was 5.25%, the mass fraction of iron was 1.75%, the mass fraction of cobalt was 0.3%, and the balance was tungsten; the second tungsten alloy electrode was a tungsten-copper alloy electrode, wherein the mass fraction of tungsten was 80% and the mass fraction of copper was 20%. (2) The steel substrate and the first tungsten alloy electrode and the second tungsten alloy electrode are subjected to surface pretreatment. Before formal deposition, the first tungsten alloy electrode and the second tungsten alloy electrode are pre-discharge activated respectively. (3) The steel substrate surface is subjected to first stage, second stage and third stage of electric spark deposition in sequence, wherein: the first stage and second stage use the first tungsten alloy electrode, and the third stage uses the second tungsten alloy electrode; The first stage is carried out under an argon leading atmosphere, the deposition voltage is 30-40 V, the deposition capacitance is 60-80 μF, and the effective deposition time per unit area is 0.2-0.6 min / cm 2 After the first stage is completed, the discharge is stopped and argon blowing is carried out for 5-30 s; The second stage is carried out in an air dominant atmosphere, the deposition voltage is 50-70 V, the deposition capacitance is 100-140 μF, and the effective deposition time per unit area is 0.6-3.8 min / cm 2 ; after the second stage is completed, the discharging is stopped and argon blowing is carried out for 5-30 s; The third stage is carried out under an argon atmosphere, the deposition voltage is 30-45 V, the deposition capacitance is 60-90 μF, and the effective deposition time per unit area is 0.2-0.6 min / cm 2 ; The sum of the effective deposition time per unit area of the three deposition stages is 1-5 min / cm 2 The three deposition stages adopt different scanning directions and set the track lap rate to form a cross-scan path, and a tungsten alloy wear-resistant coating containing yttrium oxide is formed on the surface of the steel substrate.

2. The method of claim 1, wherein, Before formal deposition, the area to be deposited is pre-purged with argon gas at a rate of 5-20 L / min for 30-120 s; during the first and third stages of deposition, the argon gas flow rate is 5-15 L / min; during the period between the two stages when the discharge is stopped, the argon gas flow rate is 5-20 L / min.

3. The method of claim 1, wherein, With a capacitive energy storage type electric spark deposition apparatus, the energy E = 1 / 2CU 2 characterizes the single theoretical energy storage, where C is the deposition capacitance and U is the deposition voltage, the single theoretical energy storage of the second phase being higher than that of the first and third phases, to form a low-high-low discharge energy program.

4. The method of claim 1, wherein, The three deposition stages are cross-scanned with increasing trajectory overlap rates: the first stage is a parallel scan along the set 0° direction with an adjacent trajectory overlap rate of 30-50%; the second stage is a cross-scanned scan with the adjacent trajectory overlap rate of 40-70% relative to the first stage rotated by 90°; and the third stage is a cross-cover scan with the adjacent trajectory overlap rate of 50-80% relative to the first stage along the 45° or 135° direction.

5. The method of claim 4, wherein, The trajectory overlap rate η is determined by η=(bs) / b×100%, where b is the average width of a single sedimentary trajectory and s is the distance between the center lines of adjacent sedimentary trajectories.

6. The method of claim 1, wherein, In step (2), the pre-discharge activation involves pre-discharging the first tungsten alloy electrode and the second tungsten alloy electrode on the sacrificial steel test piece, respectively. The pre-discharge voltage is 30~40 V, the pre-discharge capacitance is 60~80 μF, and the pre-discharge time is 5~30 s, so that the working ends of the first tungsten alloy electrode and the second tungsten alloy electrode enter a stable discharge state.

7. The method of claim 1, wherein, The particle size of tungsten powder, nickel powder, iron powder, and cobalt powder in the first tungsten alloy electrode, and the particle size of tungsten powder and copper powder in the second tungsten alloy electrode are all 40~60 μm; the mixing powder of the two electrodes is pressed at a pressure of 45~55 MPa, and the sintering temperature after pressing is 1500~1600 ℃, and the sintering time is 30~40 min; the particle size of the yttrium oxide powder is 50~100 nm.

8. The method of claim 1, wherein, The wear-resistant coating was found to contain Cu in its elemental composition by EDS analysis, and the Fe mass content was higher than the W mass content, with an Fe / W mass ratio of 1.01 to 1.

87.

9. The method of claim 1, wherein, The resulting wear-resistant coating contains α-W, α-Fe, γ-Fe(W) and α-Cu phases. The interface between the coating and the steel substrate has a gradient transition zone between W and Fe elements, and the coating thickness is greater than 15 μm.

10. The method of claim 1, wherein, The steel base is CrNi3MoVA steel, 45 steel, Q235 steel, 40Cr steel or H13 steel, the surface of the steel base is pretreated by sequentially polishing with 240#, 400#, 600# and 800# sandpaper, polishing with a grinding paste with a particle size of 2.5 μm, and ultrasonic cleaning with acetone for 5-15 min and drying; when the first tungsten alloy electrode and the second tungsten alloy electrode are subjected to surface pretreatment, the first tungsten alloy electrode and the second tungsten alloy electrode are respectively processed into shapes suitable for electric spark deposition clamping, sequentially polished with 240#, 400#, 600# and 800# sandpaper, polished with a 2.5 μm grinding paste, and then ultrasonic cleaned with acetone for 5-15 min and dried.

Citation Information

Patent Citations

  • Tungsten cobalt carbide-copper-fluoride self-lubricating wear-resistant coating and preparation method thereof

    CN102190911A

  • Preparation method of nano yttrium oxide dispersion strengthening tungsten alloy

    CN103173641A

  • Multi-element-doped oxide-dispersion-strengthened tungsten-based alloy and preparation method and application thereof

    CN113106279A

  • Electrode material for electric discharge machining and method for production thereof

    CN1711366A